Characterization of AhR agonists reveals antagonistic activity in European herring gull (Larus argentatus) eggs - Muusse, Martine; Christensen, Guttorm; Gomes, Tania; Kocan, Anton; Langford, Katherine; Tollefsen, Knut Erik; Varikova, Lenka; Thomas, Kevin V. (Science of The Total Environment, 2015)
European herring gull (Larus argentatus) eggs from two Norwegian islands, Musvær in the south east and Reiaren in Northern Norway, were screened for dioxins, furans, and dioxin-like and selected non-dioxin-like polychlorinated biphenyls (PCBs), and subjected to non-target analysis to try to identify the aryl hydrocarbon receptor (AhR) agonists, responsible for elevated levels measured using the dioxin responsive chemically activated luciferase expression (DR-CALUX) assay.Eggs from Musvær contained chemically calculated toxic equivalent (WHO TEQ) levels of between 109 and 483pgTEQ/glw, and between 82 and 337pgTEQ/glw was determined in eggs from Reiaren. In particular PCB126 contributed highly to the total TEQ (69-82%). In 19 of the 23 samples the calculated WHO TEQ was higher than the TEQ. Using CALUX specific relative effect potencies (REPs), the levels were lower at between 77 and 295pg/glw in eggs from Musvær and between 56 and 223pg/glw in eggs from Reiaren, which were higher than the TEQ in 16 of the 23 samples. However, the means of the REP values and the TEQ were not significantly different. This suggests the presence of compounds that can elicit antagonist effects, with a low binding affinity to the AhR. Non-target analysis identified the presence of hexachlorobenzene (HCB) (quantified at 9.6-185pg/glw) but neither this compound nor high concentrations of PCB126 and non-dioxin-like PCBs could explain the differences between the calculated TEQ or REP values and the TEQ.Even though, for most AhR agonists, the sensitivity of herring gulls is not known, the reported levels can be considered to represent a risk for biological effects in the developing embryo, compared to LC50 values in chicken embryos. For human consumers of herring gull eggs, these eggs contain TEQ levels up to four times higher than the maximum tolerable weekly intake.